Multi-Criteria Decision-Making Problem for Energy Storage Technology Selection for Different Grid Applications - Ander Zubiria; Álvaro Menéndez; Hans-Jürgen Grande; Pilar Meneses; Gregorio Fernández (Energies, 2022)
Grid stability and supply security need to be maintained when generation and consumption mismatches occur. A potential solution to this problem could be using Energy Storage Technologies (EST). Since many alternatives exist, appropriate technology selection becomes a key challenge. Current research focuses on ranking and selecting the most suitable technology, regardless of the grid services to be provided. In this study, a multi-criteria decision making (MCDM) problem is formulated considering fifteen selection criteria and the opinions of five energy storage experts groups. Literature and expert consultation data have been converted to triangular fuzzy (TF) numbers to cope with ambiguity and heterogeneity and eighteen technologies have been ranked applying the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The proposed method has been implemented on a software tool and assessed in four representative microgrid services of interest for the ENERISLA Project. The results show that pump hydro storage is the most suitable EST for frequency regulation, time shifting and seasonal storage applications, while flywheels best suit inertial response. It is concluded that the proposed methodology provides an intuitive framework for EST selection under multi-agent uncertainty and different grid application scenarios.